Analysis of Inclusion Teaching Methods On Driving Ball Skills - Syaifullah Amin Batubara; Liliana Puspa Sari (Educational Sciences Journal, 2024)
The purpose of this study was to see the analysis of the inclusive teaching method on the achievement of dribbling skills in Class VII students of SMP Negeri 29 Medan in the 2020/2021 academic year. The location of this research was carried out at SMP Negeri 29 Medan. The subjects in this study were all Grade VII-5 students of SMP Negeri 29 Medan for the 2020/2021 academic year, which consisted of 30 students. The method in this research is an experimental method with one group pretest and posttest design techniques using a portfolio sheet. Data analysis was carried out by data reduction carried out by looking at the influence of certain variables on other variables carried out in class VII-5 students of SMP Negeri 29 Medan in the academic year 2020/2021 during the covid-19 period there were changes in the achievement of dribbling skills through the inclusion teaching method. The success of learning is viewed from the comparison of the classical passing standards of PJOK learning that have been determined by the school with the learning achievement carried out. Based on the results of data analysis, aspects of development and student needs can be obtained according to the situations faced by the Covid-19 period and the application of learning is carried out in a variety and innovative way to create an effective learning atmosphere even during the Covid-19 period.